Evaluation of treatment effectiveness and 10-year cardiovascular disease risk level in hypertensive outpatients - Aliyu Samaila, Umar Idris Ibrahim, Aminu Ahmed Biambo, Bilkisu Muhammad Tambuwal (Journal of Applied Pharmaceutical Science, 2024)
Hypertension represents a substantial risk factor for the development of cardiovascular disease (CVD), stroke, and chronic kidney disease. CVD stands as the primary cause of global mortality. This study employed a prospective cross-sectional design spanning 4 weeks. Data were collected using a pro forma designed to capture patients’ sociodemographic and clinical information. Prescribers’ adherence to anti-hypertensive prescription guidelines, as per the JNC8 guideline, and patients’ attainment of target blood pressure (BP) goals were assessed. Framingham 10-year CVD risk score estimation was employed to estimate patients’ 10-year CVD risk levels. Among the patients, 51 (59.3%) had anti-hypertensive prescriptions that adhered to the JNC8 guidelines. However, a majority, 54 (62.8%), failed to achieve their JNC8 target BP goals, and 44 (51.2%) exhibited intermediate 10-year CVD risk levels. Furthermore, 71 (98.6%) of the patients did not receive the recommended statin and/or aspirin therapy, despite its necessity. An association was found between patients’ achievement of JNC8 target BP goals and their 10-year CVD risk levels. The majority of patients received anti-hypertensive prescriptions that aligned with JNC8 guidelines. Nonetheless, most of them did not attain their JNC8 target BP goals and exhibited intermediate to high 10-year CVD risk levels.
Keywords: Hypertension, treatment, effectiveness, cardiovascular disease, risk